PENERAPAN SANKSI TERHADAP LARANGAN PERKAWINAN SEPUPU SEKALI MASYARAKAT DAYAK KANAYATN DI DUSUN PENAWAR DESA SEKILAP KECAMATAN MANDOR KABUPATEN LANDAK - NIM. A1011191041, KAROLINA KURARAH (Fakultas Hukum Universitas Tanjungpura, 2022)
AbstractMarriage custom is an important event for the life of the Dayak Kanayatn indigenous people. Marriage is a holy and sacred thing to establish a life and death relationship until death is separated so that there are customary prohibitions when carrying out marriages which are seen in the family tree. The prohibition of first cousin marriage is a marriage that is still related by blood, this is considered taboo because it does not respect the ancestors and hurts the hearts of indigenous peoples. The problem in this study is how the application of sanctions to couples who carry out first-cousin marriages has not been fully implemented in acc ordance with customary provisions, this is because there are several factors that trigger the occurrence of first-cousin marriages in that place.In this study the authors formulated the problem of